Molecular Analysis of Activation-Induced Cytidine Deaminase Gene in Immunoglobulin-E Deficient Patients - Sergio Roa; Maria Isidoro-Garcia; Ignacio Davila; Elena Laffond; Felix Lorente; Rogelio Gonzalez-Sarmiento (Clinical and Developmental Immunology)
Understanding how class switch recombination (CSR) is regulated to produce immunoglobulin E (IgE) has become fundamental because of the dramatic increase in the prevalence of IgE-mediated hypersensitivity reactions. CSR requires the induction of the enzyme AICDA in B cells. Mutations in AICDA have been linked to Hyper-IgM syndrome (HIGM2), which shows absence of switching to IgE as well as to IgG and IgA. Although isolated IgE deficiency is a rare entity, here we show some individuals with normal serum IgM, IgG, and IgA levels that had undetectable total serum IgE levels. We have analyzed the AICDA gene in these individuals to determine if there are mutations in AICDA that could lead to selective IgE deficiency. Conformational sensitive gel electrophoresis (CSGE) and sequencing analysis of AICDA coding sequences demonstrated sequence heterogeneity due to 5923A/G and 7888C/T polymorphisms, but did not reveal any novel mutation that might explain the selective IgE deficit.